Photosynthesis Characteristics of Tomato Plants and Its’ Responses to Microclimate in New Solar Greenhouse in North China - Haijun Liu; Mengxuan Shao; Li Yang (Horticulturae, 2023)
With the increasing demand for vegetable fruits, vegetable plants are moved to protected structures for achieving high production and economic revenue, especially in undesirable seasons. In North China, tomato crops, as widely consumed vegetables, are now increasingly planted in solar greenhouses (GH), especially in the winter period. To improve the microclimate inside GH in winter, a sunken solar greenhouse was used recently. This study was to evaluate the photosynthetic characteristics of tomato plants and its responses to the inside microclimate in this new GH. In this experiment, the plant transpiration (E) and photosynthesis (Pn) rates of healthy and diseased plants were measured from July to December for three growth seasons in a commercial GH in North China. Results show both E and Pn were positively related to inside radiation and vapor pressure deficit. The stomata conductance to E (gsw) and Pn (gtc) performed relatively constant during daytime, and weakly related to inside microclimate. The parameters of E, Pn, gsw and gtc were greatly reduced for diseased plants in summer because of the heat shock. The water use efficiency at the leaf level, the ratio of Pn to E, was higher for solar radiation of 400–500 W m−2, temperature of 20–30 °C, relative humidity of higher than 80%, and vapor pressure deficit of less than 2.0 kPa. The results of this study could help farmers in the region of 30 to 40 degrees north latitude to enhance the growth of tomato crops in winter by using this sunken solar greenhouse.